Analisis Kelayakan Usaha Penggilingan Padi di Desa Polenga Kecamatan Watubangga Kabupaten Kolaka - Musdalifah, Musdalifah; Surni, Surni; Sadimantara, Fahria Nadiryati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
Â This research aims todetermine the feasibility of rice mills in the village polenga Watubangga District of Kolaka. This research has been conducted in the village of Polenga Subdistrict Kolaka Watubangga there in January to finish in 2019.The population in this study were people who had businesses rice mills as many as 10 rice milling business, Samples are a business owner in the village Polenga rice mill which is considered to represent as many as eight rice mills active effort. The sampling technique in this study using the Random Sampilng. The data used are primary data and secondary data.Based on the analysis and discussion of the rice mill in the village of the District Polenga Watubangga Kolaka economically feasible to continue this case demonstrated the value of eligibility obtained from rice milling business of BEP calculation obtained production is 1,956 kg and BEP Rp5,865 / kg. Then the values obtained Return on investment amounted to 27,87%, Because ROI> and bank interest rates RC ratio> 1 with nuse values of R / C ratio of 1.27, the effort was worth it because the larger the ratio, the more value RC worth the effort to do. This means that the rice milling business in the village of the District Polenga Watubangga Kolaka profitable and economically feasible to be developed.